The physiology of training for high performance - MacDougall, D.; Sale, D. (University Press, 2014)
This book is the only text to provide a rigorous, evidence-based understanding of the physiological bases behind training for high performance sport. It •Illuminates the processes that cause and control the body's adaptive response to training, •Combines the theoretical and applied aspects of physical training to explain which stimuli are most effective in triggering particular adaptations, •Examples and Sample Programs demonstrate how to apply the concepts developed to real-world training scenarios, The book is written by internationally-renowned exercise scientists, both extensively published in peer-reviewed journals and books, and both former athletes, coaches, and training consultants for Olympic and professional teams. An Online Resource Centre features additional resources for lecturers and students, enhancing the educational value of the text. Success for an athlete depends on their ability to perform at their best when it matters most. Performance depends on the athlete's body having acquired the most beneficial adaptations for their sport. But how can an athlete or coach be sure that training results in the desired adaptations?